Tourist arrivals from Germany to Poland in the years 2000-2018 - Krzysztof Parzych; Rafał Gotowski; Wiktoria Karczewska (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
This study addresses the issue of inbound tourism from Germany to Poland. The analysis of the issue was made on the basis of statistical data of the Local Data Bank of the Central Statistical Office of Poland based on data on the number of German tourists and the number of overnight stays granted to them in individual voivodships. In the years 2000, 2010, 2018.